Memories from 5th World Congress of Music Therapy, 1985, Genoa - Bright, Ruth; Galińska, Elżbieta; Hesser, Barbara; Moreno, Joseph; Oldfield, Amelia; Skille, Olav; Wagner, Gabriela (Voices: A World Forum for Music Therapy, 2010)
A collection of memories from 5th World Congress of Music Therapy, 1985, Genoa